2019
DOI: 10.1111/his.13817
|View full text |Cite
|
Sign up to set email alerts
|

Utility of CD123 immunohistochemistry in differentiating lupus erythematosus from cutaneous T cell lymphoma

Abstract: 2019) Histopathology 74, 908-916. https://doi.org/10.1111/his.13817 Utility of CD123 immunohistochemistry in differentiating lupus erythematosus from cutaneous T cell lymphomaAims: Histopathological overlap between lupus erythematosus and certain types of cutaneous T cell lymphoma (CTCL) is well documented. CD123 + plasmacytoid dendritic cells (PDCs) are typically increased in lupus erythematosus, but have not been well studied in CTCL. We aimed to compare CD123 immunostaining and histopathological features in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 41 publications
7
42
0
10
Order By: Relevance
“…The diagnosis of SPTCL requires strong clinicopathologic correlation in order to exclude more aggressive alpha‐beta T‐cell lymphomas, such as progressive mycosis fungoides and entities subsumed under peripheral T‐cell lymphoma, NOS. SPTCL can also show both clinical and histopathologic overlap with cutaneous autoimmune panniculitides, in particular LEP 7,8,35 While this important distinction can be aided by the identification of cytotoxic T‐lymphocytes with enlarged, hyperchromatic nuclei rimming individual adipocytes, a relative paucity of CD4 cells and B‐cell aggregates, Ki‐67 hotspots, 35,36 and an absence of CD123‐positive plasmacytoid dendritic cell clusters, 37,38 some patient have clinically and histopathologically ambiguous presentations, including those who ultimately develop HLH 5,7,8 . Another subset of patients with SPTCL includes patients with underlying autoimmune diatheses including systemic lupus erythematosus 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of SPTCL requires strong clinicopathologic correlation in order to exclude more aggressive alpha‐beta T‐cell lymphomas, such as progressive mycosis fungoides and entities subsumed under peripheral T‐cell lymphoma, NOS. SPTCL can also show both clinical and histopathologic overlap with cutaneous autoimmune panniculitides, in particular LEP 7,8,35 While this important distinction can be aided by the identification of cytotoxic T‐lymphocytes with enlarged, hyperchromatic nuclei rimming individual adipocytes, a relative paucity of CD4 cells and B‐cell aggregates, Ki‐67 hotspots, 35,36 and an absence of CD123‐positive plasmacytoid dendritic cell clusters, 37,38 some patient have clinically and histopathologically ambiguous presentations, including those who ultimately develop HLH 5,7,8 . Another subset of patients with SPTCL includes patients with underlying autoimmune diatheses including systemic lupus erythematosus 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Such cases may mimic various inflammatory dermatoses, notably cutaneous lupus erythematosus. 28 In their study, Chen et al demonstrated a significantly higher percentage of CD123+ plasmacytoid dendritic cells in cutaneous lupus erythematosus than in mycosis fungoides[Figure 3], more frequently comprising ≥20% of the entire infiltrate and forming clusters of ≥15 CD123+ plasmacytoid dendritic cells. 28 Recently, Roda et al described a case of chronic cutaneous lupus erythematosus that showed histopathological features highly suggestive of mycosis fungoides.…”
Section: In Differentiating the Alopeciasmentioning
confidence: 95%
“…28 In their study, Chen et al demonstrated a significantly higher percentage of CD123+ plasmacytoid dendritic cells in cutaneous lupus erythematosus than in mycosis fungoides[Figure 3], more frequently comprising ≥20% of the entire infiltrate and forming clusters of ≥15 CD123+ plasmacytoid dendritic cells. 28 Recently, Roda et al described a case of chronic cutaneous lupus erythematosus that showed histopathological features highly suggestive of mycosis fungoides. 29 Band-like CD123+ plasmacytoid dendritic cells at the dermo-epidermal junction (>10% of the inflammatory infiltrate) served as a useful clue to the diagnosis of chronic cutaneous lupus erythematosus in addition to the presence of increased dermal mucin deposition and basement membrane zone thickening Examining plasmacytoid dendritic cells in 28 dermatomyositis and 27 lupus erythematosus biopsies, one study demonstrated consistently greater numbersof CD123+ plasmacytoid dendritic cells and larger plasmacytoid dendritic cell percentages in the overall infiltrate in discoid lupus erythematosus (CD123+ cells represented 30% or more of the infiltrate in 12/20 cases) and subacute cutaneous lupus erythematosus lesions (CD123+ cells represented at least 20% of the infiltrate in 5/7 cases) than in dermatomyositis skin lesions (19/28 biopsies showed only rare or up to 5% CD123+ cells in the infiltrate).…”
Section: In Differentiating the Alopeciasmentioning
confidence: 95%
See 2 more Smart Citations